Synthesis of a High‐Capacity NiO/Ni Foam Anode for Advanced Lithium‐Ion Batteries. Issue 11 (24th November 2020) - Song, Youngseok; Hwang, Junesun; Lee, Sukyung; Thirumalraj, Balamurugan; Kim, Jae-Hun; Jenei, Péter; Gubicza, Jenő; Choe, Heeman
Abstract : In the article, number 2000351, the group of Jeno Gubicza and co‐workers revealed that the Ni foam fabricated via freeze casting in combination with thermal oxidation is a promising canditate as an anode material in Li ion batteries. The as‐processed Ni foam anode demonstrated good cycling and rate performance during charging/discharging process.